Dendrons containing boric acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate covalently attached to silica-coated magnetite for the expeditious synthesis of Hantzsch esters - Mahsa Sam (Nature Portfolio, 2021)
Abstract A new multifunctional dendritic nanocatalyst containing boric acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate covalently attached to core–shell silica-coated magnetite (Fe3O4@SiO2@PTS-THEIC-(CH2)3OB(OH)2) was designed and properly characterized by different spectroscopic or microscopic methods as well as analytical techniques used for mesoporous materials. It was found that the combination of both aromatic π–π stacking and boron–oxygen ligand interactions affords supramolecular arrays of dendrons. Furthermore, the use of boric acid makes this dendritic catalyst a good choice, from corrosion, recyclability and cost points of view. The catalytic activity of Fe3O4@SiO2@PTS-THEIC-(CH2)3OB(OH)2, as an efficient magnetically recoverable catalyst, was investigated for the synthesis of polyhydroacridines (PHAs) as well as polyhydroquinolines (PHQs) via one-pot multicomponent reactions of dimedone and/or ethyl acetoacetate, different aldehydes and ammonium acetate in EtOH under reflux conditions. Very low loading of the catalyst, high to quantitative yields of the desired PHAs or PHQs products, short reaction times, wide scope of the substrates, eliminating any toxic heavy metals or corrosive reagents for the modification of the catalyst, and simple work-up procedure are remarkable advantages of this green protocol. An additional advantage of this magnetic nanoparticles catalyst is its ability to be separated and recycled easily from the reaction mixture with minimal efforts in six subsequent runs without significant loss of its catalytic activity. This magnetic and dendritic catalyst can be extended to new two- and three-dimensional covalent organic frameworks with different applications.